Real Conditions for Unrealistic Obligations: The Case of Judicial Obligations in the Homeless Population - Marques, Jacqueline; Piedade, Ana Maria; Verissímo, Preciosa (European Journal of Social Science Education and Research, 2024)
This qualitative study aimed to analyse the suitability of the living conditions of the homeless population for fulfilling their judicial obligations. To this end, three categories of analysis were constructed: i) characterisation of the population; ii) perception of homeless people, which includes their view of the conditions for fulfilling judicial obligations and their impact on their lives; iii) perception of professionals, namely the suitability of judicial obligations and suggestions. The data was collected by interviewing: i) all the homeless people complying with judicial obligations monitored by a DGRSP team who came to the services between November and March 2024; ii) the professionals who monitor these situations. All the homeless people and professionals interviewed agree that their conditions are not suitable for them to fulfil their legal obligations imposed by the court. For homeless people, the cause of this difficulty is centred on the lack of housing. Another reason was the need for more sensitivity and suitability of the services to their real needs. It is interesting to realise that for professionals, housing is not directly mentioned as the main reason for the inadequacy of the obligations imposed. For them, the main difficulty centres on this population's personal and social characteristics, namely their instability and multiplicity of problems. They believe intervention with this population should be systematic and personalised (rather than generalised) to create the necessary conditions for compliance with any obligation. Only one individual considers that the fulfilment of obligations positively impacts their life, while the rest consider that it has no positive impact, so they see it only in its punitive aspect. This disparity in perceptions highlights a crucial question about the effectiveness and nature of judicial measures regarding the goal of social reintegration.The research highlights the fact that judicial requirements often ignore the context and living conditions of homeless people and emphasises the significant impact of housing, economic and health conditions on the ability of homeless people to comply with judicial measures.
Keywords: homelessness; judicial obligations; social intervention in justice; human rights